Tourism Effect towards Youth Resiliency in Ubud, Gianyar, Bali - Retnaningtyas Susanti; Pande Made Kutanegara (International Journal of Tourism, Heritage and Recreation Sport, 2019)
Tourism is the economical heart of Ubud, Gianyar, Bali’s society. Almost 90% working age population work as tourism worker and almost 50% of the village’s area is used as business space. This condition pushes resiliency from many aspects of population, especially youth. Tourism affects culture and custom in youth, especially in their obligation of Pura in their environment and the demands of up-to-date culture covering it. This research was done for 4 months, started in August to December 2018. The data collection method used was in-depth interview supported by survey results. In-depth interview was done to the public figures, youth participating in Sekaa Teruna Teruni (STT), village government, and Banjar manager. Questionnaire was given to 12th grade students of higher education (SMA/SMK) in Ubud. Survey data was processed using regression analysis and describes as supporting data for the in-depth interview. The result of the research shows that Ubud youths have resiliency tendency in a positive way towards tourism in their environment. They do not leave customs and cultures as feared by many people regarding tourism erosion in Bali which getting stronger. The youth knows that customs and cultures have to go together with tourism. Tourists come to Ubud because of the cultures there. Most of the youth knows that tourism is their future, and so does their customs obligations and cultures. Thus, the two are better managed and processed without leaving one or the other.